The impact of special economic zones on exporting behavior - Ronald B. Davies; Arman Mazhikeyev (University College Dublin, UCD School of Economics, 2015)
Using firm level data from Africa and Asia, we estimate the impact of being in a special economic zone (SEZ) on a firm's probability of exporting, export intensity, and value of exports. At the extensive margin, we find that SEZ firms in open economies are 25% more likely to export than their non-SEZ counterparts, with a large negative effect in closed economies. At the intensive margin, we find that SEZs increase the value of exports, but only in countries with barriers to imports where the estimate increase is 3.6%. Thus, the estimated effect of introducing an SEZ can be meaningful, but is heavily contingent on the local economic environment.
Keywords: F14; J16; 330; Exporting; Trade Barriers; Special Economic Zones